Immunogenicity Following Two Doses of the BBIBP-CorV Vaccine and a Third Booster Dose with a Viral Vector and mRNA COVID-19 Vaccines against Delta and Omicron Variants in Prime Immunized Adults with Two Doses of the BBIBP-CorV Vaccine - Jira Chansaenroj; Nungruthai Suntronwong; Sitthichai Kanokudom; Suvichada Assawakosri; Ritthideach Yorsaeng; Preeyaporn Vichaiwattana; Sirapa Klinfueng; Lakana Wongsrisang; Donchida Srimuan; Thaksaporn Thatsanatorn; Thanunrat Thongmee; Chompoonut Auphimai; et al. (Vaccines, 2022)
Coronavirus disease 2019 (COVID-19) booster vaccination is being comprehensively evaluated globally due to waning immunity and the emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants. Therefore, this study aimed to evaluate antibody responses in individuals vaccinated with two doses of the BBIBP-CorV vaccine and to explore the boosting effect of the different vaccine platforms in BBIBP-CorV-primed healthy adults, including a viral vector vaccine (AZD122) and mRNA vaccines (BNT162b2 and mRNA-1273). The results showed that in the BBIBP-CorV prime group, the total receptor-binding domain (RBD) immunoglobulin (Ig) and anti-RBD IgG levels waned significantly at three months after receiving the second dose. However, after the booster, RBD-specific binding antibody levels increased. Neutralizing antibody measured by a surrogate neutralization test showed inhibition over 90% against the SARS-CoV-2 delta variant but less than 70% against the omicron variant after the third dose on day 28. All booster vaccines could induce the total IFN-ɣ T-cell response. The reactogenicity was acceptable and well-tolerated without serious adverse events. This study supports the administration of the third dose with either a viral vector or mRNA vaccine for BBIBP-CorV-primed individuals to stimulate antibody and T-cell responses.